A review of the tropical approach in cryptography. Issue 1 (2nd January 2023) - Ahmed, K.; Pal, S.; Mohan, R.
Abstract: In this article, we survey and analyze the role of tropical semirings in key-exchange protocols proposed in the past decade. We also present new ideas on cryptanalysis of some tropical key agreement techniques suggested during this period.